2018
DOI: 10.1523/jneurosci.1713-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Dissociable forms of uncertainty-driven representational change across the human brain

Abstract: Environmental change can lead decision makers to shift rapidly among different behavioral regimes. These behavioral shifts can be accompanied by rapid changes in the firing pattern of neural networks. However, it is unknown what the populations of neurons that participate in such "network reset" phenomena are representing. Here, we investigated the following: (1) whether and where rapid changes in multivariate activity patterns are observable with fMRI during periods of rapid behavioral change and (2) what typ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 47 publications
6
71
0
Order By: Relevance
“…Two recent studies that clearly dissociate salience from learning using a generative structure like our oddball condition have suggested that the latter may be the case (d' Acremont & Bossaerts, 2016;Nassar, Bruckner, & Frank, 2019a). One recent idea that attempts to rectify differences between the relationship between brain activity and learning rate observed across different statistical environments is that learning rate adjustments are implemented through changes in the active latent state (Nassar, Bruckner, & Frank, 2019a;Nassar, McGuire, Ritz, & Kable, 2019b;Wilson, Takahashi, Schoenbaum, & Niv, 2014). When changes to this latent state are carried forward in time (eg.…”
Section: Changepoint Oddballmentioning
confidence: 97%
See 3 more Smart Citations
“…Two recent studies that clearly dissociate salience from learning using a generative structure like our oddball condition have suggested that the latter may be the case (d' Acremont & Bossaerts, 2016;Nassar, Bruckner, & Frank, 2019a). One recent idea that attempts to rectify differences between the relationship between brain activity and learning rate observed across different statistical environments is that learning rate adjustments are implemented through changes in the active latent state (Nassar, Bruckner, & Frank, 2019a;Nassar, McGuire, Ritz, & Kable, 2019b;Wilson, Takahashi, Schoenbaum, & Niv, 2014). When changes to this latent state are carried forward in time (eg.…”
Section: Changepoint Oddballmentioning
confidence: 97%
“…oddballs) then they could drive reductions in learning rate. Within this framework, the fronto-parietal control network could be thought of as providing a signal to load a new state representation, whereas regions including the orbitofrontal cortex seem to reflect the newly loaded state itself (Nassar, McGuire, Ritz, & Kable, 2019b). An important question raised by our work is where individual differences would fall in such a mechanistic process.…”
Section: Changepoint Oddballmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, these hypothesis RDMs were related to the empirical RDM through multiple linear regression analysis, where a coefficient was estimated relating each hypothesis RDM to empirical RDMs allowing us to parcel out variance in representational distances due to multiple factors in the same model 33 . The lower-triangle of all hypothesis RDMs were extracted as vectors, mean centered, and included as predictors, along with an intercept term, in a multiple linear regression analysis to calculate beta coefficients relating each hypothesis RDM to the empirical RDM.…”
Section: Representational Similarity Analysismentioning
confidence: 99%